Systematics of the genus Rhacophorus (Amphibia, Anura): identity of red-webbed forms and description of a new species from Assam - Bordoloi, Sabitry; Bortamuli, Tutul; Ohler, Annemarie (Zootaxa, 2007)
The taxonomic status of Rhacophorus maculatus Anderson, 1871 and its replacement names (alloneonyms) Rhacophorus bimaculatus Boulenger, 1882 and Rhacophorus bipunctatus Ahl, 1927 is assessed and a lectotype (lectophoront) for this nomen is designated. Morphological evidence supports the nomen Rhacophorus htunwini Wilkinson et al., 2005 being a junior subjective synonym of Rhacophorus maculatus Anderson, 1871. Rhacophorus rhodopus Liu & Hu, 1960 is considered a valid nomen with a new junior subjective synonym, Rhacophorus namdaphaensis Sarkar & Sanyal, 1985. A new species of red-webbed Rhacophorus is described which can be distinguished by the other species by the presence of web between fingers, green dorsal coloration and red web on feet, the absence of blackish spots on web and on flanks, the absence of complete web between fingers and the absence of distinct dermal appendages on forelimbs, tarsi and feet. A key to the red-webbed species of Rhacophorus is given.